Training healthcare professionals to administer Goal Attainment Scaling as an outcome measure - Benignus Logan; Andrea K. Viecelli; Elaine M. Pascoe; Bonnie Pimm; Laura E. Hickey; David W. Johnson; Ruth E. Hubbard (SpringerOpen, 2024)
Abstract Background Goals generated by Goal Attainment Scaling (GAS) can be used as an outcome measure to promote person-centred research and care. There are no training packages which support its use outside of the rehabilitation discipline. This paper describes the development and evaluation of a training package to support the implementation of GAS as an outcome measure in healthcare research. The training package consisted of classroom teaching, a training manual for self-directed learning, one-on-one simulation and hot reviews. It was developed for the GOAL Trial, a randomised controlled trial assessing a Comprehensive Geriatric Assessment's effectiveness in enabling frail older people living with chronic kidney disease to attain their goals. Training participants were invited to complete pre- and post-training online evaluation surveys. Results Forty-two healthcare professionals attended an initial online classroom teaching, with 27 proceeding to administer GAS to GOAL Trial patients. Response rates for the online pre- and post-training surveys were 95% and 72%, respectively. Prior to training, only 15% of participants reported being able to appropriately scale and troubleshoot GAS goals. Post-training this was 92%. There was 100% participant satisfaction for the training manual, one-on-one simulation, and hot reviews. Conclusions This training package helps ensure healthcare professionals administering GAS have adequate knowledge and skills. It has the potential for adoption as a guide to support the implementation of GAS by other researchers seeking to embrace persont-centred principles in their work.